1995
DOI: 10.1016/s1010-7940(05)80108-3
|View full text |Cite
|
Sign up to set email alerts
|

Can the location of the large septal artery be predicted?

Abstract: The aim of this study is to establish anatomical landmarks for the trajectory of the large septal artery. Thirty hearts were dissected, 20 of which had no cardiac pathology and the remaining with different cardiac conditions. One large septal artery was located in 27 of these hearts, two large septal arteries in 2 and three large septal arteries in 1. For all cases there existed one large septal artery in the lower border of the anterior limb of the septomarginal trabecula. When more than one large septal arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…A study conducted by Melo et al 28 showed that the human heart possess 7 anterior septal branches on average, although some hearts displayed less than 5 branches, while others possessed 13 branches, in contrast with a study performed by Hosseinpour et al 29 which had the presence of 4 anterior septal branches, on average. In 2% of cases, the ST blood supply originated from an anastomosis between the first anterior septal artery and branches of the right coronary artery.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A study conducted by Melo et al 28 showed that the human heart possess 7 anterior septal branches on average, although some hearts displayed less than 5 branches, while others possessed 13 branches, in contrast with a study performed by Hosseinpour et al 29 which had the presence of 4 anterior septal branches, on average. In 2% of cases, the ST blood supply originated from an anastomosis between the first anterior septal artery and branches of the right coronary artery.…”
Section: Discussionmentioning
confidence: 87%
“…Knowledge of the anterior septal branches anatomy is significant to operations such as Ross procedure, Konno procedure (correction of Fallot's tetralogy), resection of obstructive muscular subaortic stenosis, and enlargement of restrictive ventricular septal defects, as they require incisions on the upper portion of the interventricular septum 28,29 . Injury of these vessels can cause myocardial damage and arrhythmia, due to its relation with the ST and right branch of the atrioventricular bundle, in rare cases, iatrogenic injuries can cause sudden death 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Gross was the first researcher to observe the constant occurrence of the artery of the SMT (ramus limbi dextri) in 1921, and other researchers have confirmed its presence. [3][4][5][6][7][8][9][10][11][12] It is often described as a branch of one of the septal arteries, which branches off from the anterior descending artery. While studying the position of the artery of the trabecula, Reig et al noticed that in 20 cases (71%) this artery originated in the 2 nd anterior septal artery, in 5 cases (18%) in the 1 st anterior septal artery, and in 2 cases (7%) in the 3 rd one.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to Melo et al, this artery is located in the lower part. 4 Reig et al state that the 2 nd path which arteries may follow to the SMT is an oblique path. It extends from the right side of the SMT toward the apex of the heart until it reaches the place where the SMT separates from the septum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation